CLIMATE VARIABILITY AND ECONOMIC PERFORMANCE IN EGYPT USING ARDL APPROACH - Ayatullah Mazen; Fatma Mabrouk; Ahmed A. Mashaal; Wafaa A. B. Eid; Moataz Eliw (Journal of Animal and Plant Sciences, 2026)
<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">T<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">he research issue is to gauge the effect of climate change on the economic performance of Egypt and which environmental factors have the greatest restrictive effect on growth. This paper examines how climate change will affect economic growth in Egypt between 1990 and 2024, through the Autoregressive Distributed Lag (ARDL) model. The primary measure of economic performance is the GDP per capita, which is analyzed in connection with some major climate variables carbon dioxide emissions, precipitation, and average temperature and other economic variables that include investment, arable land, and natural resource rents. The ARDL model is especially the right tool to use in this analysis because it allows variables that used to be integrated into a time series of differing order, which is prevalent in climatic and economic time series. The findings demonstrate that there are evident differences in short-run and long-run effects. The effect of increasing temperatures in the short run is a decline in the economic output indicating a productivity loss associated with heat in agriculture and labor intensive sectors. The role of precipitation in economic growth in both long and short is always positive because it underlines that the availability of water is a key limiting factor on the development of Egypt. The relationship between carbon dioxide outputs and long-run economic growth is positive and significant, which demonstrates the fact that Egypt remains relying on energy-intensive production. Growth is also supported by arable land, but recent trends have indicated that there is slowdown in land expansion. The error correction process implies quite rapid adaptation to long-run equilibrium, and the diagnostic tests prove the stability of the model estimated. The results show that there is increasing conflict between economic development in the short term and the climate threat in the long term. The shrinking water supply and the mounting climatic stress imply that the growth will be necessary to be sustained with the help of immediate policy actions, especially in the area of water management, energy conversion, and climate adjustments.
Keywords: Climate change; Economic growth; Water scarcity; ARDL model; CO₂ emissions; Egypt